2017
DOI: 10.1371/journal.pone.0176941
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control in people with type 2 diabetes mellitus during and after cancer treatment: A systematic review and meta-analysis

Abstract: BackgroundCancer and Diabetes Mellitus (DM) are leading causes of death worldwide and the prevalence of both is escalating. People with co-morbid cancer and DM have increased morbidity and premature mortality compared with cancer patients with no DM. The reasons for this are likely to be multifaceted but will include the impact of hypo/hyperglycaemia and diabetes therapies on cancer treatment and disease progression. A useful step toward addressing this disparity in treatment outcomes is to establish the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Prostate Cancer database (PCBaSe) Sweden 3.0 is based on the National Prostate Cancer Register (NPCR) of Sweden, which became nationwide in 1998 and covers 98% of all newly diagnosed cases of PCa, as compared with the Swedish Cancer Register. 15 16 NPCR includes information on date of diagnosis, age at diagnosis, tumour stage and differentiation, serum levels of prostate-specific antigen at time of diagnosis. Using the Swedish personal identity number, five PCa-free men from the general population in Sweden were randomly selected within sets of men who matched the index case on birth year and county of residence and included in a PCa-free control cohort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prostate Cancer database (PCBaSe) Sweden 3.0 is based on the National Prostate Cancer Register (NPCR) of Sweden, which became nationwide in 1998 and covers 98% of all newly diagnosed cases of PCa, as compared with the Swedish Cancer Register. 15 16 NPCR includes information on date of diagnosis, age at diagnosis, tumour stage and differentiation, serum levels of prostate-specific antigen at time of diagnosis. Using the Swedish personal identity number, five PCa-free men from the general population in Sweden were randomly selected within sets of men who matched the index case on birth year and county of residence and included in a PCa-free control cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Swedish personal identity number, five PCa-free men from the general population in Sweden were randomly selected within sets of men who matched the index case on birth year and county of residence and included in a PCa-free control cohort. 15 Both men with PCa and those in the control cohort were subsequently linked to a series of national healthcare registers and demographic databases, including the National Diabetes Register (NDR) and the Prescribed Drug Register (PDR). PCBaSe Traject includes all data in PCBaSe 3.0 but has additional linkages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent meta-analysis in 2017 revealed that patients with T2DM treated with melbine have a lower risk of gastric cancer than those who were not treated with melbine ( 14 ). In addition, perioperative glycemic control can not only reduce the incidence rate of postoperative complications, but also can benefit patients in the long-term prognosis because early blood glucose control can delay the deterioration of tumor to some extent and improve the survival of patients ( 15 , 16 ). These studies are consistent with our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Most people know little about the possible relationship between radiation exposure and diabetes (17). For example, among 8 articles including a systematic review and meta-analysis of 1863 T2DM patients reported by Pettit et al which identified and analyzed the current evidence on glycemic control (HbA1c) during and after cancer treatment, the effect of radiation on glycemic control is not mentioned (18). However, it has been considered by the International Commission for Radiation Protection as one factor involved in multifactorial diseases (19).…”
Section: Radiation Environmentmentioning
confidence: 99%